Finite-Time Observer-Based Sliding Mode Control Design for a Rotary Inverted Pendulum System - Kadri, Kamel; Boudjema, Farès; Ouahab, Badis; Tibermacine, Imad Eddine; Bouzid, Yasser (Journal of Applied Nonlinear Dynamics, 2026)
This paper presents the development of a Finite-Time Disturbance Observer-Based Sliding Mode Controller (FTDOBSMC) for controlling and stabilizing a Rotary Inverted Pendulum (RIP) system. The FTDOBSMC is composed of three key elements: a finite-time disturbance observer for estimating disturbances, a nonlinear sliding surface designed to enhance convergence speed during the sliding motion phase of sliding mode control, and a Combinatorial Reaching Law (CRL) that integrates the power reaching law and the variable speed reaching law. This combination helps minimize chattering and improve system robustness. The stability of the RIP system is validated using Lyapunov theory. Notably, simulation results demonstrate that the FTDOBSMC achieves faster convergence of the closed-loop system to the origin, maintains the pendulum angle closer to the stable equilibrium point, and exhibits superior robustness against various types of time-varying disturbances.